Mindfully wise leadership the secrets of today's leaders - Tsuk, Keren (Rowman & Littlefield Publishers, 2021)
Mindfully Wise Leadership presents timely, implementable, and easy mindfulness practices for the modern workplace. Here, learn how to incorporate mindful practices to increase productivity, innovation, and employee engagement through examples taken from some of the largest and most successful companies.